Calibrating the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) for detecting alcohol-related problems among Canadian, UK and US soldiers: cross-sectional pre-deployment and post-deployment survey results. Issue 5 (2nd May 2023) - Duffy, Farifteh Firoozmand; Sudom, Kerry; Jones, Margaret; Fear, Nicola T; Greenberg, Neil; Adler, Amy B; Hoge, Charles W; Wilk, Joshua E; Riviere, Lyndon A
Abstract : Objectives: Excessive alcohol use can bring about adverse health and work-related consequences in civilian and military populations. Screening for excessive drinking can help identify individuals at risk for alcohol-related problems who may require clinical interventions. The brief validated measures of alcohol use such as the Alcohol Use Disorders Identification Test (AUDIT), or abbreviated AUDIT-Consumption (AUDIT-C), are often included in military deployment screening and epidemiologic surveys, but appropriate cut-points must be used to effectively identify individuals at risk. Although the conventional AUDIT-C cut-points ≥4 for men and ≥3 for women are commonly used, recent validation studies of veterans and civilians recommend higher cut-points to minimise misclassification and overestimation of alcohol-related problems. This study aims to ascertain optimal AUDIT-C cut-points for detecting alcohol-related problems among serving Canadian, UK and US soldiers. Design: Cross-sectional pre/post-deployment survey data were used. Settings: Comprised Army locations in Canada and UK, and selected US Army units. Participants: Included soldiers in each of the above-mentioned settings. Outcome measures: Soldiers' AUDIT scores for hazardous and harmful alcohol use or high levels of alcohol problems served as a benchmark against which optimal sex-specific AUDIT-C cut-points were assessed. Results: Across the three-nation samples, AUDIT-C cut-points of ≥6/7 for men and ≥5/6 for women performed well in detecting hazardous and harmful alcohol use and provided comparable prevalence estimates to AUDIT scores ≥8 for men and ≥7 for women. The AUDIT-C cut-point ≥8/9 for both men and women performed fair-to-good when benchmarked against AUDIT ≥16, although inflated AUDIT-C-derived prevalence estimates and low positive predictive values were observed. Conclusion: This multi-national study provides valuable information regarding appropriate AUDIT-C cut-points for detecting hazardous and harmful alcohol use, and high levels of alcohol problems among soldiers. Such information can be useful for population surveillance, pre-deployment/post-deployment screening of military personnel, and clinical practice.